Quantitative Investigation of Wildlife Trafficking Supply Chains: A Review. (February 2023) - Keskin, Burcu B.; Griffin, Emily C.; Prell, Jonathan O.; Dilkina, Bistra; Ferber, Aaron; MacDonald, John; Hilend, Rowan; Griffis, Stanley; Gore, Meredith L.
Highlights: We review illicit wildlife trafficking (IWT) through an operations and supply chain lens. We provide a list of challenges related to illicit wildlife trafficking. We discuss OR/SC areas that can offer solutions to IWT-related issues. We explore three IWT problem domains with differing objectives and constraints. Abstract: The illicit wildlife trade is a pervasive and global problem that has far-reaching impacts on both society and the environment. Aside from threatening numerous species around the world and acting as a potential disease transmission vector for several zoonotic diseases, including the COVID-19 pandemic, this complex system is often linked with other illicit networks such as drugs, weapons, and human trafficking. The annual monetary value of wildlife trafficking is estimated to be over twenty billion USD, and, unfortunately, wildlife trafficking has several unique characteristics that make it difficult to disrupt in an effective and efficient manner. There has been much research and media awareness around wildlife conservation and moral issues surrounding the illicit wildlife trade, but little is known about the supply chain structures and operations of these illicit networks, especially from a quantitative, analytical perspective. This research reviews wildlife trafficking through an operations and supply chain lens. By understanding the unique challenges faced in impeding wildlife trafficking, we present opportunities to resolve them using analytical techniques. We provide the groundwork for future developments in detection, interdiction, reduction, and possibly, elimination of illicit wildlife trade.